Assessment of alluvial aquifer conditions during a construction phase for a deep excavation. Issue 1 (1st January 2023) - Ghulami, Masoud; Gourbesville, Philippe
Abstract: The Var low valley and its unconfined alluvial aquifer is the main water resource for around 600, 000 inhabitants who live in the French cities and towns near the river mouth, such as Nice and St Laurent du Var. Several commercial and residential complexes are planned to be built in the downstream floodplain areas of the Var River and close to the Nice airport. Some of these buildings may have an impact on the groundwater table and consequently on the supply of drinking water. In this study, the groundwater flow was simulated using MIKE FEFLOW numerical model to assess the impacts of new development projects by estimating the drawdown of groundwater table due to the planned pumping activities as well as tracing the trajectories of groundwater movements to make sure the salt intrusion will not happen. The study focuses on a planned building, near well line used for water supply. The building was initially designed with several underground floors as parking lots. The model is developed and validated using the available piezometric data of 2010-2012 for the study area. The model was able to simulate the hydraulic head with a good precision (the Nash Sutcliffe Efficiency coefficient of 0.7 and higher). As the local groundwater level is very high and only a few meters below the ground surface, during the construction period of the foundation, the site must be kept dry, and the water should be pumped out. It will normally last around six months. However, this construction period is the most critical stage and will have serious impacts on the groundwater table, but our simulation results suggest that even after the construction period, the groundwater table will be dropped and consequently the salt intrusion into the groundwater due to the short distance of the site to the sea will be continued. Therefore, different foundation levels were tested to find the best solution.